2017
DOI: 10.1016/j.cels.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

An Optimized Shotgun Strategy for the Rapid Generation of Comprehensive Human Proteomes

Abstract: SummaryThis study investigates the challenge of comprehensively cataloging the complete human proteome from a single-cell type using mass spectrometry (MS)-based shotgun proteomics. We modify a classical two-dimensional high-resolution reversed-phase peptide fractionation scheme and optimize a protocol that provides sufficient peak capacity to saturate the sequencing speed of modern MS instruments. This strategy enables the deepest proteome of a human single-cell type to date, with the HeLa proteome sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
577
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 463 publications
(592 citation statements)
references
References 71 publications
14
577
1
Order By: Relevance
“…For example, two dimensional chromatography fractionation (8,9) and increased reverse phase column length (10,11) were reported to enhance peak capacity for proteome analyses. Improvements in quadrupole performance through higher resolution and scanning rate have enabled more efficient isolation and transmission of target ions with narrow isolation windows in turn reducing chimeric tandem mass spectra (12).…”
Section: Introductionmentioning
confidence: 99%
“…For example, two dimensional chromatography fractionation (8,9) and increased reverse phase column length (10,11) were reported to enhance peak capacity for proteome analyses. Improvements in quadrupole performance through higher resolution and scanning rate have enabled more efficient isolation and transmission of target ions with narrow isolation windows in turn reducing chimeric tandem mass spectra (12).…”
Section: Introductionmentioning
confidence: 99%
“…26 Using a modified offline high-pH fractionation technique, Bekker-Jensen et al demonstrated that proteomic analysis can reach a similar depth as the next-generation RNA-seq technology. 25 These approaches reduced the complexity of peptide mixtures and enabled deep analysis of cellular proteomes. Substantial increments of instrument time and sample consumption are needed to compensate for the increased number of protein IDs, which not only reduce the throughput of the experiment, but also impede the automation of the entire procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Such sensitivity is sufficient to detect the 2500 most abundant proteins in a single human cell 18 , which should be able to identify different states of cellular differentiation. Furthermore, unlike immunoassays that require significant amounts of development time and rely on the availability of high-quality antibodies 7,8 , cPRISM-SRM is relatively easy to implement in research laboratories with commercially available standard instruments 32 .…”
Section: Discussionmentioning
confidence: 99%